(untitled) (Agora for Physical Education and Sport, 2022)
This research presents the life history of a Cantabrian woman footballer in the first division, highlighting the experiences, supports and barriers in her sporting practice from her earliest childhood to the present day. This is a qualitative study carried out through a biographical-narrative interview. The instrument used is a script of questions designed ad hoc and divided into three blocks referring to the three techniques: self-presentation, semi-structured interview and photographic technique. A chronological order of the narrative was used for the analysis of the information. The main results and their discussion reflect the importance of supports, giving special value to family, teammates and coaches. The most notable barriers are related to impediments linked to gender differences. Consequently, we consider it is necessary to highlight a reality that triggers a true transformation at a macro level in the football field.